(3JLQjO CUhd GdefWb heSGFdgs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s ((3eMeO Hf CHj GdWjH GdeGdci s)
(3ChdgG (B:s
(3hHYO aEfG GQOfG Cf fLQO CUhd GdefWb heSGjdg Ydi GdJQJjH s
(3BNQgG (B:s
(3hbO Jchf eTcdGJ heNGdaGJ JGeI Ch fGbUI ai GdCdaGX s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B346s
(3eUOQ GbJfGA GdCUd (B:s
(3edj edc (B_ (3EjQGf (B(640) s
Keywords: (3GdadSaI hGdefWbs